Susceptibility to Rubella Among Tertiary Students in Punjab, India: A Cross-Sectional Study - Atul Khajuria (International Journal of Vaccines, 2025)
Rubella is a mild illness; however, it becomes severely threatening when associated with congenital rubella syndrome (CRS) for women of childbearing age. India still faces endemic rubella despite available vaccines, and vaccination coverage is low. Tertiary students are near reproductive age, and as a socially active and mobile population, they are highly susceptible to rubella and can aid in disease transmission. This study tried to fill the existing data gap by evaluating 2,500 tertiary students from Punjab, India on their awareness and rubella vaccination history and susceptibility.
Keywords: India; Punjab; Rubella; congenital rubella syndrome; health awareness; students from tertiary education institutions; vaccination coverage